PROMOTION OF STATISTIC INFORMATION FOR CONSTANT DEVELOPMENT OF AGRICULTURE AND PROTECTION OF LIFE ENVIRONMENT - Vicentijevic, Dragisa; Jelic, Svetlana (Economics of Agriculture, 2006)
Modern approach of protection of life environment and constant economy and social development is not possible without quality and accurate information, generally speaking. Also is unquestionable that statistic information, data and indicators are very important base for detection of changes which indicates the state of human environment and especially quality, structure and quantity of natural resources (land, water potential, biodiversity, general climate etc.). Statistic information is also important for presentation of demographic changes, structure and disposition of human resources which are very important for agriculture development. Information resources, especially statistic, provides possibility to perceive methods and ways of protection of life environment, all in function of constant development of agriculture, especially for establishing organic agriculture and methods of production of organic food which is perfectly safe and healthy for domestic and foreign market.